Penerapan Manajemen Sumber Daya Manusia Berbasis Syariah Dalam Meningkatkan Kinerja Karyawan - Putri, Elsa Amanda Aulia; Veninda Ariesta Mawarni; Hamidatul Aulia; Rafika Meilia Sari (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to examine the implementation of Sharia-based human resource management (HRM) in an effort to improve employee performance. This research is motivated by the importance of human resource management that emphasizes not only productivity but also moral and spiritual values derived from Islamic teachings. The method used in this study is a qualitative approach through literature review, examining various concepts of Sharia-based HRM, including the recruitment, selection, employment agreements, and performance evaluation processes. The results indicate that the implementation of Sharia-based HRM can improve employee quality by integrating the values of honesty, trustworthiness, fairness, and professionalism into every management process. Furthermore, an objective recruitment and selection system, accompanied by fair and transparent employment contracts, contributes to the creation of a conducive work environment. The implications of this study indicate that organizations that implement Sharia principles in human resource management are not only able to improve employee performance but also build an ethical, harmonious, and sustainable work culture.